Tajdid (renewal) and Islah (reform) tendencies of Islam in the post-communist Albania - Shehu, Fatmir Mehdi (2018)
This paper seeks to study the revival of Islam in Albania through Tajdid (renewal) and Islah (reform) tendencies carried out by the Albanian Muslim community after the fall of communism in 1990. The objective of this study is to show the role of Tajdid and Islah activities towards the restoration of Islam in the post-communist Albania. This research is very significant as it highlights the renewal process of Islam in Albania. This paper starts with a brief introduction on Albanians and their religious identity, and then, continues with the examination of: (1) restoration of Islamic educational institutions and places of worship, and (2) reformation of Muslim’s identity and belongingness. The descriptive and analytical methods are utilized. The expected outcomes of this scientific study will add new insights to the exiting literature on Tajdid and Islah tendencies of Islam in Muslim world especially in Albania.